2023
DOI: 10.3390/biology12030480
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment and Metformin Improve Metabolic Functions, Hippocampal Neuron Survival, and Hippocampal-Dependent Memory in High-Fat/High-Sucrose Diet-Induced Type 2 Diabetic Rats

Abstract: Background: The Western-style diet-induced type 2 diabetes mellitus (T2D) may eventually trigger neurodegeneration and memory impairment. Thus, it is essential to identify effective therapeutic strategies to overcome T2D complications. This study aimed to investigate the effects of environmental enrichment (EE) and metformin interventions on metabolic dysfunctions, hippocampal neuronal death, and hippocampal-dependent memory impairments in high-fat/high-sucrose (HFS) diet-induced T2D rats. Methods: Thirty-two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
(59 reference statements)
2
3
0
Order By: Relevance
“…Compared with Janumet group and Control group, there was a statistically significant decrease in serum insulin levels observed in Diabetic group. This finding was consistent with previous result (16,18) . In the current study, the decreased serum insulin levels observed in the Diabetic group may have been caused by the STZ administration.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Compared with Janumet group and Control group, there was a statistically significant decrease in serum insulin levels observed in Diabetic group. This finding was consistent with previous result (16,18) . In the current study, the decreased serum insulin levels observed in the Diabetic group may have been caused by the STZ administration.…”
Section: Discussionsupporting
confidence: 94%
“…Hippocampal tissue in Diabetic+Janumet group revealed apparent improvement in the thickness of layers and shape of cells but still showing very few shrunken pyramidal cells in CA1 and CA3 and also the granular layer of dentate gyrus restored its normal structure. These beneficial effects were consistent with other studies (1,16) .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations